162k views
5 votes
4th time posting this...........

4th time posting this...........-example-1

1 Answer

2 votes

Answer:

D is the correct representation.


((4x^2 + 2x)/(x^(2)+x-2) )/( (8x^2 +4x)/(3x^2 +10x+8) ) =
{((3x+4))/(2(x-1))

Explanation:

Here, the given equation is:


((4x^2 + 2x)/(x^(2)+x-2) )/( (8x^2 +4x)/(3x^2 +10x+8) )

here, numerator =
{(4x^2 + 2x)/(x^(2)+x-2) }

and denominator =
(8x^2 +4x)/(3x^2 +10x+8)

Solving numerator and denominator separately, we get

NUMERATOR:


{(4x^2 + 2x)/(x^(2)+x-2) } \implies(2x(2x +1))/(x^(2) + 2x-x-2 ) \\\implies(2x(2x +1))/((x+2)(x-1) )

Denominator:


(8x^2 +4x)/(3x^2 +10x+8)  = (4x(2x+1))/(3x^2 +6x+ 4x+8)\\ \implies (4x(2x+1))/(3x(x+2)+ 4(x+2))  =  (4x(2x+1))/((3x+4)(x+2))

Hence, the transformed fraction is:


((2x(2x +1))/((x+2)(x-1) ))/((4x(2x+1))/((3x+4)(x+2)))  = {(2x(2x +1))/((x+2)(x-1) )} *{((3x+4)(x+2))/(4x(2x+1))

or, implied fraction is
{((3x+4))/(2(x-1))

Hence, D is the correct representation.

User Arocketman
by
5.7k points